Strategi Bank Riau Kepri Syariah dalam Memanfaatkan Transaksi Rupiah Digital dan Blockchain Upaya Mewujudkan Pelayanan Prima Kepada Nasabah - Zulkarnain Zulkarnain; Abdul Ghoni (SYNERGY: Jurnal Bisnis dan Manajemen, 2025)
The use of digital technology in the economic sector is currently experiencing very rapid development, not to mention the banking sector such as Bank Riau Kepri Syariah. The purpose of writing this article is to analyze the strategy implemented by Bank Riau Kepri Syariah in utilizing digital rupiah transactions and blockchain technology to improve excellent service to customers. This research uses the SWOT analysis method to identify strengths, weaknesses, opportunities and threats in the application of digital and blockchain technology in the sharia banking sector. The research results explain that BRK Syariah, in utilizing digital rupiah and block chain technology to improve the quality of excellent service to customers, is implementing a strategy designed to suit current needs, which is useful for developing BRK Syariah's service strategy in facing the challenges of the continuously developing digital banking industry